Maternity and Mobility: Immigrant Women and Their Ambulant Sales in the Pages of Buenos Aires Illustrated Magazines, 1898-1918 - Prudant-Soto, E (UNIV ESTADUAL LONDRINA, 2019)
The article analyzes the speeches and representations that operated behind the "maternalization" of immigrant women who served as street vendors in the pages of two illustrated magazines commercialized in Buenos Aires at the turn of the 19th to the 20th century: Caras y Caretas, and PBT. In the itinerant bodies of these women, exposed to the representational exercise that awoke their double trajectory of mobility - transatlantic migration and wandering daily through the streets of the Argentine capital - the primary function was inscribed to them by the State in the construction of the nation: being mothers of future citizens. Its origin, reproductive role and the precariousness in which they lived inside the metropolis, were the filters from which magazines make known the significant potential of their incursion into public space as informal workers. The article seeks to elucidate the mechanisms through which patriarchal discourse and its correlation of ethnicity and class, femininity representations were disseminated in certain print media that relate the experience of the sales women with the cultural project that accompanied the formation of the nation in Argentina. Methodologically, the proposed analysis, based on the historical approach with a gender perspective, reconstructs the characteristics attributed to the street sales women, through a detailed study of the images and texts referenced by the magazines Caras y Caretas (1898-1920) and PBT (1904-1918).